Native Renal Biopsy: An Essential Diagnostic Tool in Systemic Lupus Erythematosus - Basu, Keya; De, Suparna; Karmakar, Subhrajyoti; Sengupta, Moumita; Sircar, Dipankar; Roychowdhury, Arpita; Bandopadhyay, Manimoy (Annals of Pathology and Laboratory Medicine, 2018)
Background – Systemic lupus erythematosus (SLE) is a connective-tissue disorder of autoimmune aetiology and presented with broad range clinical manifestation due to multisystem involvement. In spite of overall reduction in morbidity due to recent therapy, renal involvement is the leading cause of disease related mortality. Materials and Method We conducted a cross-sectional observational study to assess clinicopathological findings and to identify the prognostic association of histopathological parameters with advanced clinical stage. We included 31 patients met the diagnostic criteria of SLE according to revised criteria of the American College of Rheumatology (ACR) for SLE in 1997. Each native renal biopsy was examined by two trained pathologists by light microscopy and was classified using ISN/RPS 2003 lupus nephritis classification system. The Kruskal–Wallis test was performed for comparisons between multiple groups. Result Pedal edema were found to be the most common clinical presentations. . Female preponderance is noted in present study with male: female ratio 1:9.3. We found diffuse proliferative glomerulonephritis (class IV) as most frequent class with incidence rate of 54.8%. After combination of the variables along with different classes of lupus nephritis, significant statistical association was observed in endocapillary proliferation and neutrophillic in filtration as activity predicting factors. Silent LN has been observed in class II as well as in class IV disease also The most common deposited immunoglobulin was IgG. Conclusion Renal biopsy remains the main diagnostic tool in identification of exact stage of involvement because clinical staging may not accurately corroborate with histopathological staging.